Far-right politics in Europe - Camus, Jean-Yves, 1958-; Lebourg, Nicolas, 1974- (The Belknap Press of Harvard University Press, 2017)
In Europe today, staunchly nationalist parties such as France's National Front and the Austrian Freedom Party are identified as far-right movements, though supporters seldom embrace that label. More often, "far-right" is pejorative, used by liberals to tar these groups with the taint of fascism, Nazism, and other discredited ideologies. Jean-Yves Camus and Nicolas Lebourg's critical look at the far right throughout Europe--from the United Kingdom to France, Germany, Poland, Italy, and elsewhere--reveals a pre-history and politics more complex than the stereotypes suggest and warns of the challenges these movements pose to the EU's liberal-democratic order. The European far right represents a confluence of many ideologies: nationalism, socialism, anti-Semitism, authoritarianism. In the first half of the twentieth century, the radical far right achieved its apotheosis in the regimes of fascist Italy and Nazi Germany. But far-right movements have evolved significantly since 1945, as Far-Right Politics in Europe makes clear. The 1980s marked a turning point in political fortunes, as national-populist parties began winning seats in European parliaments. Since the terrorist attacks of 9/11, a new wave has unfurled, one that is explicitly anti-immigrant and Islamophobic in outlook. Though Europe's far-right parties differ in important respects, they are motivated by a common sense of mission: to save their homelands from the corrosive effects of multiculturalism and globalization by creating a closed-off, ethnically homogeneous society. Members of these movements are increasingly determined to gain power through legitimate electoral means. In democracies across Europe, they are succeeding.--